2011
DOI: 10.1371/journal.pgen.1002102
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Accumulation of Stress Response mRNAs Contributes to the Neurodegeneration Caused by Fragile X Premutation rCGG Repeats

Abstract: Fragile X–associated tremor/ataxia syndrome (FXTAS) is a neurodegenerative disorder seen in Fragile X premutation carriers. Previous studies found that Fragile X rCGG repeats are sufficient to cause neurodegeneration and that the rCGG repeat-binding proteins Pur α and hnRNP A2/B1 can modulate rCGG–mediated neuronal toxicity. To explore the role of Pur α in rCGG–mediated neurodegeneration further, we took a proteomic approach and identified more than 100 proteins that interact with Pur α. Of particular interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 41 publications
0
64
0
Order By: Relevance
“…Genetic analysis demonstrated that the RNA helicase RM62/ Lip and the actin-binding protein Hts function as modulators of rCGG repeat induced toxicity. 29 We also identified three of these proteins in our analysis GFP-Pur-α interactors in ovaries (Ypsilon Schachtel and Hsc4) or somatic S2-cells (dFmr1), despite the very different technical approaches and tissues (ovaries or cells vs. brain extract). A common conclusion of both studies is that Pur-α likely associates with mRNPs before their export from the nucleus, then travels together with the mRNP to the cytoplasm.…”
Section: Discussionmentioning
confidence: 81%
“…Genetic analysis demonstrated that the RNA helicase RM62/ Lip and the actin-binding protein Hts function as modulators of rCGG repeat induced toxicity. 29 We also identified three of these proteins in our analysis GFP-Pur-α interactors in ovaries (Ypsilon Schachtel and Hsc4) or somatic S2-cells (dFmr1), despite the very different technical approaches and tissues (ovaries or cells vs. brain extract). A common conclusion of both studies is that Pur-α likely associates with mRNPs before their export from the nucleus, then travels together with the mRNP to the cytoplasm.…”
Section: Discussionmentioning
confidence: 81%
“…This observation suggests that accumulated RNA repeats might interfere with the proper delivery of mRNAs from nuclei to cytosol, eventually affecting gene expression. As a matter of fact, Fragile X premutated rCGG repeats, which are responsible for Fragile X-associate tremor/ataxia syndrome (FXTAS), induce nuclear accumulation of mRNAs, including mRNAs involved in stress response, in a Drosophila model (Qurashi et al, 2011). Notably, this process is mediated by the interaction of the Drosophila homologue of the p68 RNA helicase, Rm62, with Pura, whose localization is profoundly affected by C9orf72 expression, as shown in this work, and has been suggested to play a pivotal role in C9orf72-mediated neurodegeneration in Drosophila (Xu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…All these findings indicate an important role for retrotransposition in neurodegeneration [36]. The role of Purα in rCGG-mediated neurodegeneration was further investigated by Qurashi et al [37]. They identified more than 100 proteins that interact with Purα through a proteomic approach.…”
Section: Purα and Fragile X Tremor/ataxia Syndromementioning
confidence: 96%